2015
DOI: 10.1128/iai.00196-15
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Proinflammatory β-1,6 Glucans in the Pneumocystis carinii Cell Wall

Abstract: Inflammation is a major cause of respiratory impairment during Pneumocystis pneumonia. Studies support a significant role for cell wall ␤-glucans in stimulating inflammatory responses. Fungal ␤-glucans are comprised of D-glucose homopolymers containing ␤-1,3-linked glucose backbones with ␤-1,6-linked glucose side chains. Prior studies in Pneumocystis carinii have characterized ␤-1,3 glucan components of the organism. However, recent investigations in other organisms support important roles for ␤-1,6 glucans, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 76 publications
2
35
0
Order By: Relevance
“…Populations of Pc were isolated from chronically infected rat lungs by homogenization and filtration through 10-mm filters, as we previously described (3,18). Unless otherwise noted, the remaining reagents were obtained from Sigma-Aldrich (St. Louis, MO).…”
Section: Strains and Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Populations of Pc were isolated from chronically infected rat lungs by homogenization and filtration through 10-mm filters, as we previously described (3,18). Unless otherwise noted, the remaining reagents were obtained from Sigma-Aldrich (St. Louis, MO).…”
Section: Strains and Reagentsmentioning
confidence: 99%
“…The cell surface of the pathogenic fungal species represented by Pneumocystis organisms have not been fully elucidated, but are known to contain b-1,3 and b-1,6 glucans, and the major surface mannoserich glycoproteins, variously termed major surface glycoprotein (MSG) or glycoprotein A (gpA) (3)(4)(5). We and others have shown that the Pneumocystis species contain b-glucan synthetases that can be inhibited by specific b-glucan inhibitors, such as the echinocandins, pneumocandins, and newly generated compounds (3,4,6,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cysts are ascuslike structures that consist of multiple nuclei surrounded by a fungal cell wall. ␤-1,3-Glucan and ␤-1,6-glucan serve as the structural components of the cyst wall (15,16). Trophic forms do not express ␤-glucan (15).…”
mentioning
confidence: 99%